2000
DOI: 10.1159/000018799
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Index Is the Best Predictive Factor for Survival of Patients with Resected Hepatocellular Carcinoma

Abstract: Background: In patients with hepatocellular carcinoma (HCC), tumor recurrence is not infrequent after resection. It is presumed that characteristics of the tumor such as cellular malignancy might influence the prognosis of the patients in association with tumor stage and radicality of the procedure. Methods: Univariate and multivariate analyses were used to retrospectively determine the clinicopathologic factors potentially related to survival in 40 patients who underwent hepatectomy for HCC. Results: In univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…When these findings are compared, MI was higher at 24 (2.6%) and 48 h (6.4%) in our study [21]. It is reported that MI is an important parameter providing information about survival [28]. Several authors have shown that this proliferation-associated antigen is expressed during all active parts of the cell division cycle (G1, S, G2, and M) but is absent in resting cells (G0) [29,30].…”
Section: Discussionsupporting
confidence: 44%
“…When these findings are compared, MI was higher at 24 (2.6%) and 48 h (6.4%) in our study [21]. It is reported that MI is an important parameter providing information about survival [28]. Several authors have shown that this proliferation-associated antigen is expressed during all active parts of the cell division cycle (G1, S, G2, and M) but is absent in resting cells (G0) [29,30].…”
Section: Discussionsupporting
confidence: 44%
“…Selzner and Clavien (2000) found the MIs at the 24 and 48 h, 2% and 3%, respectively. It is reported that MI is an important parameter providing information about survival (Ouchi et al, 2000). Several authors have shown that this proliferation-associated antigen is expressed during all active parts of the cell division cycle (G1, S, G2, and M) but is absent in resting cells (G0) (Assy and Minuk, 1997;Assy et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions mitotic activity does not occur in undamaged liver, whereas mitotic activity increases in liver with tissue damage caused by toxins or volume loss [15,33]. The MI represents the relative number of cells undergoing mitosis, and it is an important parameter providing information about the likelihood of survival [34]. In another study, mitotic cell counts in rats that underwent 70% PHx were higher at 24 and 48 h after PHx than at 72 h and later [35].…”
Section: Discussionmentioning
confidence: 99%